Anconeus Muscle-Pedicle Bone Graft With Periosteal Coverage for Osteochondritis Dissecans of the Humeral Capitellum. Issue 9 (14th September 2017) - Shimada, Kozo; Temporin, Ko; Oura, Keiichiro; Tanaka, Hiroyuki; Noguchi, Ryosuke
Background: Treatment of advanced osteochondritis dissecans (OCD) of the capitellum is controversial, especially in moderate-sized lesions. Purpose: To establish a treatment algorithm for capitellum OCD, we tried to determine the utility of and problems associated with anconeus muscle-pedicle bone graft with periosteal coverage (ABGP) for the treatment of moderate-sized articular OCD defects of the capitellum. Study Design: Case series; Level of evidence, 4. Methods: According to our protocol for elbow OCD, 16 patients (15 males, 1 female; age range, 12-17 years; mean age, 14.4 years) with a moderate-sized OCD lesion of the humeral capitellum were treated with ABGP. All patients had a full-thickness, unstable OCD lesion that was 10 to 15 mm in diameter. Clinical results and postoperative images, including radiographs and magnetic resonance imaging (MRI), were evaluated at a mean follow-up of 31 months (range, 24-66 months). Results: All but 1 patient had functional improvement after the procedure and returned to previous sporting activities within 6 months. One female patient needed 1 year for functional recovery due to development of postoperative chronic regional pain syndrome (CRPS). Two patients required additional surgery, including shaving of the protruding cartilage, and they returned to their previous level of activity. Mean arc of range of flexion-extension motion was 117° preoperatively and 129° at follow-up ( P = .031). Mean elbow function as assessed with the clinical rating system of Timmerman and Andrews was 136 preoperatively and 186 at follow-up ( P = .00012). Bony union of the graft as demonstrated by trabecular bone bridging on radiography was obtained within 3 months in all patients. Postoperative MRI was examined for 14 patients at 6 to 12 months after the procedure; the MRIs showed near-normal articular surface integrity in 9 of the 14 patients (64%) and underlying bony structure in 10 of the 14 patients (71%). Conclusion: Improvement after ABGP was obtained within 6 months in all except 1 patient, who developed CRPS. Postoperative radiography and MRI revealed near-normal articular surface integrity or underlying bony structure. This procedure is useful as a surgical option for a moderate-sized articular OCD lesion in the elbow.